GUGATAN DALAM TRILOGI INSIDEN KARYA SENO GUMIRA AJIDARMA: SEBUAH KAJIAN STRUKTURALISME GENETIK - Ferdinandus Moses (tuahtalino, 2018)
This study intends to reveal the accusation of the author to the "human values" of the Ex-East Timor issues reflected in the Trilogy Incident book by Seno Gumira Adjidarma. The Incident Trilogy is a combination of three parts consisting of a collection of short stories, novels, and essays published in 2010 by Spread Publisher. The purpose of this research is to reveal the relation between the facts of humanity, the subject collective (social facts), and the world views, as conveyed by Lucien Goldman. The approach used in this research is genetic structuralism approach, which is an approach that departs from the assumption that the structure of literary text is a reflection of people's lives. The method used in this research is descriptive method. The results of this study will reveal the building blocks of literary works, namely: 1) Humanity Facts, 2) Collective Subjects, and 3) World Views.